Novel CAD/CAM-splint-based navigation protocol enhances intraoperative maxillary position control in orthognathic surgery: a case control study - Felix Schrader; Leonardo Saigo; Norbert Kübler; Majeed Rana; Max Wilkat (Head & Face Medicine)
Abstract Background Virtual surgical planning for orthognathic surgery typically relies on two methods for intraoperative plan transfer: CAD/CAM occlusal splints and patient-specific implants (PSI). While CAD/CAM splints may offer limited accuracy, particularly in the vertical dimension, PSIs are constrained by higher costs and extended preparation times. Surgical navigation has emerged as a potential alternative, but existing protocols often involve invasive registration or lack transparent evaluation. This study introduces a novel protocol for point-based optical navigation using modified CAD/CAM splints for non-invasive registration and transparent intraoperative evaluation, assessing its effectiveness in maxillary positioning. Methods This prospective case-control study included 20 patients undergoing bimaxillary orthognathic surgery. The experimental group employed surgical navigation with modified CAD/CAM splints, while the control group used standard CAD/CAM splints. Surgical accuracy was evaluated by measuring translational and rotational discrepancies between the planned and achieved maxillary positions. A mixed ANOVA was conducted to assess other factors, aside from surgical navigation, that might influence surgical accuracy. Results Surgical navigation significantly improved accuracy in translational movements along the x-axis (right-left: -0.81 mm; p = 0.021) and z-axis (down-up: -0.82 mm; p = 0.014), as well as in yaw rotation (-0.45°; p = 0.045). Other movements also showed improved precision in the navigated group, though not statistically significant; y-axis (back-front): -0.60 mm (p = 0.094); pitch rotation: -0.70° (p = 0.071); roll rotation: -0.04° (p = 0.428). Besides the use of surgical navigation, the amount of planned movement significantly impacted surgical accuracy, although no specific factors could be identified to predict which cases would particularly benefit from surgical navigation. Conclusions Surgical navigation with modified CAD/CAM splints enhances surgical accuracy without requiring invasive procedures, offering a straightforward and transparent protocol suitable for routine clinical practice that allows intraoperative evaluation of maxillary positioning. However, the clinical significance and cost-effectiveness compared to PSI need further investigation. These findings suggest new directions for future developments, especially with advancements in mixed reality technologies, which could broaden the application of surgical navigation. Trial registration Retrospectively registered with the German Clinical Trials Register (DRKS00034795).